Health Professionals’ Knowledge And Attitude Towards Patient Confidentiality And Associated Factors - Meshal Dakhil Alanazi , Saleh Dakhel Alanazi , Mohammed Abdullrahman Alqunise , Abdullah Sulaiman Al Olaiwi , Majid Abdul Rahman Al-Nassar , Tamany Rajah J Alroyle , Mohammed Alnuqaythan (Migration Letters, 2022)
Background: Maintaining patients’ confidentiality is a crucial ethical and legal obligation for healthcare providers and a fundamental aspect of delivering high-quality care. This study seeks to evaluate the understanding, perspectives, and influencing factors among healthcare professionals regarding patients’ confidentiality, particularly in a setting with limited resources. Methods: A cross-sectional study was conducted among 423 healthcare professionals based in institutions. Stratified sampling was utilized for participant selection, and data was gathered through a structured self-administered questionnaire. Data entry was performed using Epi-data version 4.6 and analyzed using SPSS version 25. Both bi-variable and multivariable binary [1]logistic regression analyses were employed to assess the relationship between dependent and independent variables, with odds ratios, 95% confidence intervals, and P-values calculated to determine strength and statistical significance. Results: Among 410 participants, approximately 59.8% [95% CI (54.8–68.8%)] demonstrated good knowledge, and 49.5% [95% CI (44.5–54.5%)] exhibited a favorable attitude towards patient confidentiality. Factors significantly associated with healthcare professionals’ knowledge of patient confidentiality included being male (AOR = 1.63, 95% CI [1.03–2.59]), receiving training in medical ethics (AOR = 1.73, 95% CI = [1.11–2.70]), and encountering ethical dilemmas (AOR = 3.07, 95% CI [1.07–8.79]). Similarly, training in medical ethics (AOR = 2.30, 95% CI [1.42–3.72]), direct patient contact (AOR = 3.06, 95% CI [1.12–8.34]), frequent patient visits (AOR = 4.38, 95% CI [2.46–7.80]), and ethical dilemmas (AOR = 3.56, 95% CI [1.23–10.26]) were significant factors associated with healthcare professionals’ attitudes towards patient confidentiality. Conclusion: The study indicates that healthcare professionals exhibit a modest attitude but relatively good knowledge regarding patient confidentiality. Encouraging ongoing medical ethics training for healthcare workers, both pre-employment and during their tenure, could enhance their understanding and attitudes towards patient confidentiality.